2021
DOI: 10.3389/fmars.2021.713783
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Genetic Linkage Map Based on SNP Markers, QTL Mapping and Detection of Candidate Genes of Growth-Related Traits in Pacific Abalone Using Genotyping-by-Sequencing

Abstract: Pacific abalone (Haliotis discus hannai) is a commercially important high valued molluscan species. Its wild population has decreased in recent years. It is widely cultured in Korea. Traditional breeding programs have been implemented for hatchery production of abalone seeds. To obtain more genetic information for its molecular breeding program, a high-density linkage map and quantitative trait locus (QTL) for three growth-related traits was constructed for Pacific abalone. F1 cross population with two parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The qRT-PCR assay was conducted using a 2×qPCRBIO SyGreen Mix Lo-Rox kit (PCR Biosystems Ltd., UK), as described previously ( Kho et al, 2021 ). The qRT-PCR reaction mixture was prepared with cDNA template (1 μl), 10 pmol forward and reverse primer (1 μl each), SyGreen Mix (10 μl), and ultra-pure water (10 μl) in a total volume of 20 μl.…”
Section: Methodsmentioning
confidence: 99%
“…The qRT-PCR assay was conducted using a 2×qPCRBIO SyGreen Mix Lo-Rox kit (PCR Biosystems Ltd., UK), as described previously ( Kho et al, 2021 ). The qRT-PCR reaction mixture was prepared with cDNA template (1 μl), 10 pmol forward and reverse primer (1 μl each), SyGreen Mix (10 μl), and ultra-pure water (10 μl) in a total volume of 20 μl.…”
Section: Methodsmentioning
confidence: 99%
“…The qRT-PCR assay was conducted using the 2× qPCRBIO SyGreen Mix Lo-ROX kit (PCR Biosystems Ltd., London, UK) as previously described [31]. A 20 µL of qRT-PCR reaction mixture was prepared using 1 µL of cDNA template, 1 µL of each gene specific forward and reverse primer, 10 µL of SyGreen Mix, and 7 µL of DDW.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…At present, the entire abalone aquaculture industry uses hatchery-produced abalone seed. Abalone hatcheries produce seeds using conventional selection breeding [7]. Conventional phenotypical selection breeding substantially improves the growth rate of abalone.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and marker-assisted breeding is successfully used in many aquaculture species including greenshell mussel [9], Pacific oyster [10], noble scallop [11], whiteleg shrimp [12], salmon [13], Japanese flounder [14], and rainbow trout [15] to achieve higher growth and disease resistance. Regarding abalone, several studies performed genetic analysis and concluded that growth-related traits can be improved using MAS breeding [7,16]. However, the development of potential markers for growth-related traits across ages in abalone has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation